Iron-Driven Alterations on Red Blood Cell-Derived Microvesicles Amplify Coagulation during Hemolysis via the Intrinsic Tenase Complex - Delvasto-Núñez, Laura; Roem, Dorina; Bakhtiari, Kamran; van Mierlo, Gerard; Meijers, Joost C. M.; Jongerius, Ilse; Zeerleder, Sacha S. (Thrombosis and Haemostasis, 2021)
Hemolytic disorders characterized by complement-mediated intravascular hemolysis, such as autoimmune hemolytic anemia and paroxysmal nocturnal hemoglobinuria, are often complicated by life-threatening thromboembolic complications. Severe hemolytic episodes result in the release of red blood cell (RBC)-derived proinflammatory and oxidatively reactive mediators (e.g., extracellular hemoglobin, heme, and iron) into plasma. Here, we studied the role of these hemolytic mediators in coagulation activation by measuring factor Xa (FXa) and thrombin generation in the presence of RBC lysates. Our results show that hemolytic microvesicles (HMVs) formed during hemolysis stimulate thrombin generation through a mechanism involving FVIII and FIX, the so-called intrinsic tenase complex. Iron scavenging during hemolysis using deferoxamine decreased the ability of the HMVs to enhance thrombin generation. Furthermore, the addition of ferric chloride (FeCl3) to plasma propagated thrombin generation in a FVIII- and FIX-dependent manner suggesting that iron positively affects blood coagulation. Phosphatidylserine (PS) blockade using lactadherin and iron chelation using deferoxamine reduced intrinsic tenase activity in a purified system containing HMVs as source of phospholipids confirming that both PS and iron ions contribute to the procoagulant effect of the HMVs. Finally, the effects of FeCl3 and HMVs decreased in the presence of ascorbate and glutathione indicating that oxidative stress plays a role in hypercoagulability. Overall, our results provide evidence for the contribution of iron ions derived from hemolytic RBCs to thrombin generation. These findings add to our understanding of the pathogenesis of thrombosis in hemolytic diseases.
Keywords: coagulation; red blood cells; iron; hemolysis; intrinsic tenase complex